Investigation on process-properties relationship with mechanical properties of lattice-structured cellular material for lightweight application - Rosli, Nor Azwar Syahila; Hasan, Rafidah; Ng, Wai Hoe; Baharudin, Muhammad Khairi; Alkahari, Mohd Rizal (Science Publishing Corporation, 2018)
Lattice structures possess exceptional mechanical strength resulting in highly efficient load supporting systems. The lattice structure has been receiving interest in a variety of application areas and industries such as automotive, shipping and aeronautic. The metallic or polymer micro lattice structure can be categorized as lightweight and energy-absorbing structure. These characteristics are best applied to transportation part where the lightweight structure will help reduce its overall weight, thus increase the operational time since energy and cost consumption is a big concern in the industry these days. The aim of this study is to investigate relationship between process-properties and mechanical performance of polymer lattice structure. The lattice structure was designed by using SolidWorks software and fabricated using CubePro 3D printing machine. Compression test was performed by Instron 5585 universal testing machine to analyse the strength of the lattice structure. It was found that lattice structure manufactured with the setting of solid print strength, honeycomb print pattern, 70 µm layer thickness and strut diameter of 2.4 mm possesses the optimum mechanical property.